Maryland’s StateStat : A State-level Performance Management System - Dorotinsky, Bill (World Bank, Washington, DC, 2012)
Statestat is Maryland's performance measurement and management system. In use since 2007, Statestat was originally modeled after Baltimore's citistat as a way of capturing and monitoring the progress of government service delivery using frequently updated data. Through a process of continual re-evaluation by the Governor, his executive staff, and agency leadership during bi-weekly meetings, new and improved strategies emerge for delivering key public services effectively and efficiently. Located within the Governor's offices in Annapolis, a lean staff provides the logistical and analytical support for the operation. A recent visit to Statestat by the Public Sector Performance (PSP) Global Expert Team (GET) in November 2009 revealed a set of interesting findings applicable to countries developing performance management systems.